2016
DOI: 10.1111/ped.12883
|View full text |Cite
|
Sign up to set email alerts
|

High‐mobility group box‐1 release into fetal circulation from umbilical cord tissue and amniotic epithelium in fetal ischemia

Abstract: We report the case of a baby with low birthweight born by emergency caesarean section at 33 weeks 2 days' gestation due to placental abruption. High-mobility group box-1 (HMGB-1) and interleukin-17 concentration in the umbilical cord blood were high at 55.7 ng/mL and 50.7 pg/mL, respectively. On immunostaining of umbilical cord and amniotic epithelium, HMGB-1 was identified in the nuclei of vascular endothelial cells and cytoplasm of the surrounding cells in the umbilical cord. This suggests that, in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Studies of HMGB‐1 in neonates have occasionally been reported . Thus, we investigated serum HMGB‐1 in full‐term neonates with no abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies of HMGB‐1 in neonates have occasionally been reported . Thus, we investigated serum HMGB‐1 in full‐term neonates with no abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of HMGB-1 in neonates have occasionally been reported. [2][3][4][5][6][7] Thus, we investigated serum HMGB-1 in full-term neonates with no abnormalities. In 2012, we reported that the reference range of serum HMGB-1 in these neonates was 2.0-35.3 ng/mL, which was higher than that (10 ng/mL) in adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations